4(-5-7x)-3x=18+7b

Simple and best practice solution for 4(-5-7x)-3x=18+7b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(-5-7x)-3x=18+7b equation:


Simplifying
4(-5 + -7x) + -3x = 18 + 7b
(-5 * 4 + -7x * 4) + -3x = 18 + 7b
(-20 + -28x) + -3x = 18 + 7b

Combine like terms: -28x + -3x = -31x
-20 + -31x = 18 + 7b

Solving
-20 + -31x = 18 + 7b

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '20' to each side of the equation.
-20 + 20 + -31x = 18 + 20 + 7b

Combine like terms: -20 + 20 = 0
0 + -31x = 18 + 20 + 7b
-31x = 18 + 20 + 7b

Combine like terms: 18 + 20 = 38
-31x = 38 + 7b

Divide each side by '-31'.
x = -1.225806452 + -0.2258064516b

Simplifying
x = -1.225806452 + -0.2258064516b

See similar equations:

| 6x+3(-3)=9 | | 6(x-3)=2x+4x | | 3(x+2)-6x+6=0 | | -12=8+1/2 | | -40.0C=K | | 6(2)+3y=9 | | Y^2+2x-5=0 | | 13-y=29+2y | | -121-(144)= | | 4r^2+16r+12=0 | | 3/2=-7/6v+1/2+21/6 | | 3G+6= | | 5t-3=18+3(1-t) | | -(5+2k)-5(5k-6)=25 | | 8x-32+20=30-5x | | 5(-1)-3(-1)= | | y(12+5xy)dx+x(6+3xy)dy=0 | | 3G+6ifg=7 | | 12+x=12+2 | | 7(3w^1/3)(2w^1/7) | | 10x-5-8x-3= | | 2(r+3)-6(1-11r)=8r+r | | 4X(X+5)-11=4X+17X+4 | | 10n-5n=20+n+8-10n | | 0=3x^3+10x^2-27x-10 | | 2(1-7p)-3(7-6p)=27 | | 2y^2*8u*2u^3y^6= | | 5w^8u^6*2w*4u^6= | | -9-18X=-135 | | U=v-14findV | | 2/x+4=20 | | 3(4x+3)+7(6x+1)=43 |

Equations solver categories